Proceedings of the International Workshop on Semantic Web Information Management 2011
DOI: 10.1145/1999299.1999300
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-based recommendation for points of interest retrieved from multiple data sources

Abstract: Introduction of powerful mobile devices and increasing availability of online services make it possible to develop a wide range of mobile applications. Making recommendations to the users on their mobile devices based on their location is a wellknown application area of location based services. In this work we introduce an ontology based approach to find reasonable recommendations for sites (Points of Interest) like restaurants, hotels, and touristic places. We extend an existing OWL ontology in order to keep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…However, both the name and location of duplicate entries may be slightly different. Therefore, we have used a heuristic based on the approach from [9] to detect and remove duplicates: first, places are indicated as duplicates when they are located closer than 5 meters of each other. Second, to detect additional duplicates of a given place p all neighboring places of the same type in a range of 100 meter were selected as candidate duplicates.…”
Section: A Collecting Places Of Interestmentioning
confidence: 99%
“…However, both the name and location of duplicate entries may be slightly different. Therefore, we have used a heuristic based on the approach from [9] to detect and remove duplicates: first, places are indicated as duplicates when they are located closer than 5 meters of each other. Second, to detect additional duplicates of a given place p all neighboring places of the same type in a range of 100 meter were selected as candidate duplicates.…”
Section: A Collecting Places Of Interestmentioning
confidence: 99%
“…To automatically estimate the semantic type of places, some authors have suggested to classify places based on their name [15], the content of webpages which contain the place name [3] or both [16]. However, only a few broad place types were considered in these works and the proposed methods have only been tested on small test sets ranging from 59 to 1160 places.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the name and location of duplicate entries may be slightly different. Therefore, we have used a heuristic based on the approach from [15] to detect and remove duplicates: first, places are indicated as duplicates when they are located closer than 5 meters to each other. Second, to detect additional duplicates of a given place p all neighboring places of the same type in a range of 100 meter were selected as candidate duplicates.…”
Section: Collecting Places Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The location-based service is the service provided based on the location information of user (Ozdikis et al, 2011) and map data as the background to show the position visually and the information regarding the POI (point of interest) showing the position of main objects are necessary (Rae et al, 2012).…”
Section: Introductionmentioning
confidence: 99%